2000
DOI: 10.1021/jm000249r
|View full text |Cite
|
Sign up to set email alerts
|

(−)-Spiro[1-azabicyclo[2.2.2]octane-3,5‘-oxazolidin-2‘-one], a Conformationally Restricted Analogue of Acetylcholine, Is a Highly Selective Full Agonist at the α7 Nicotinic Acetylcholine Receptor

Abstract: Neuronal nicotinic acetylcholine receptors are members of the ligand-gated ion channel receptor superfamily and may play important roles in modulating neurotransmission, cognition, sensory gating, and anxiety. Because of its distribution and abundance in the CNS, the alpha 7 nicotinic receptor is a strong candidate to be involved in some of these functions. In this paper we describe the synthesis and in vitro profile of AR-R17779, (-)-spiro[1-azabicyclo[2.2. 2]octane-3,5'-oxazolidin-2'-one] (4a), a potent full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
100
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(102 citation statements)
references
References 21 publications
1
100
0
Order By: Relevance
“…DMXBA also attenuated the sensory gating deficits observed in rats that were reared in isolation (O'Neill et al, 2003), an animal neuro-developmental model of schizophrenia (Geyer et al, 1993). Furthermore, both DMXBA (Kem, 2000), and the full a7 nAChR agonist AR-R17779 (Mullen et al, 2000), are able to replicate the beneficial effects observed with nicotine on working memory (Felix and Levin, 1997;Levin and Simon, 1998). In contrast, and perhaps somewhat surprisingly, recent studies in rats showed that AR-R17779 had no effect on attention in the 5-CSR task (Grottick and Higgins, 2000;Grottick et al, 2003;Hahn et al, 2003a).…”
Section: Discussionmentioning
confidence: 93%
“…DMXBA also attenuated the sensory gating deficits observed in rats that were reared in isolation (O'Neill et al, 2003), an animal neuro-developmental model of schizophrenia (Geyer et al, 1993). Furthermore, both DMXBA (Kem, 2000), and the full a7 nAChR agonist AR-R17779 (Mullen et al, 2000), are able to replicate the beneficial effects observed with nicotine on working memory (Felix and Levin, 1997;Levin and Simon, 1998). In contrast, and perhaps somewhat surprisingly, recent studies in rats showed that AR-R17779 had no effect on attention in the 5-CSR task (Grottick and Higgins, 2000;Grottick et al, 2003;Hahn et al, 2003a).…”
Section: Discussionmentioning
confidence: 93%
“…AR-R 17779, an AstraZeneca product, is an acetylcholine analogue with full agonist properties at the α7 nicotinic cholinergic receptor. This compound does not enhance the inhibition of startle in DBA/2 mice [123,124,125] or improve accuracy and speed of response on a five-choice serial reaction time [126,127]. ABT-418, has some agonist properties at the α7 nicotinic cholinergic receptors, but is a less potent agonist than nicotine [128] and restores deficient auditory gating in DBA/2 mice as well as rats with fimbria-fornix lesions, but similar to nicotine, fails to produce continued improvement with a second dose [54].…”
Section: Dmxba As a Prototype Drugmentioning
confidence: 85%
“…The steric and electronic requirements of this site are met by structurally diverse classes of compounds as reviewed recently (Toyohara et al, 2010a), and potential ligands originate from for example benzylidene anabasein compounds such as GTS-21 , or the quinuclidine framework such as AR-R-17779, both shown in Fig. 2 (Bodnar et al, 2005;Mazurov et al, 2005;Mullen et al, 2000;Tatsumi et al, 2005). A recently developed highly selective fluorescent α7 nicotinic receptor ligand is restricted to in vitro studies because of its chemical structure (Hone et al, 2010).…”
Section: Eldar Rosenfeld and Anat Keslermentioning
confidence: 99%